Relationship between anger expression and anger control with conflict management styles among college students - Mat Najib, Norazizalina; Zakaria, Noor Syamilah; Ismail, Asmah; Mohamad Yusop, Yusni (Human Resource Management Academic Research Society, 2023)
Anger leads to aggressive behaviour if one unable to control it. This study aims to determine relationship between anger expression and anger control with conflict management styles among college students. Participants consist of 54 college students. Two sets of questionnaires used in this study are the State Trait Anger Expression Inventory II and the Thomas Killman Conflict Mode Instrument. Data were analysed using descriptive and Pearson correlation analyses. Findings showed that there is no significant relationship between anger expression inwards with conflict management styles. However, there is significant relationship between anger expression outwards, anger control inwards and anger control outwards with conflict management styles. Implication of this study is for the mental health professionals to help adolescents in assessing their anger to express and control the anger effectively.